Dispositifs De Prévention Contre Le Risque D’infiltration Des Eaux Souterraines Dans Les Ouvrafes De Constructions - Tahar, Ayadat (European Scientific Journal, ESJ, 2017)
For constructing sustainable geotechnical structures, it is recommended to design these structures within a perspective of performance, adaptability and durability. This article briefly describes the various geotechnical risks and the actions to be taken to reduce or eliminate these risks. It examines in more detail the problem of risks associated with groundwater infiltration in construction structures. It discusses the various causes and the measures to be taken to eliminate this risk. Finally, the article introduces the preventive measures against groundwater infiltration for two case studies, namely a sports complex and a residential building. The study also includes precautions to be taken for protecting buildings against ground swelling caused by shale rock.